Recreational Demand for Kovai Kutralam Ecotourism Centre:A Travel Cost Method - Raj, Varadha; Kavigeetha, C. D.; Ashok, K. R.; Chinnadurai, M. (Indian Forester, 2017)
Kovai Kutralam Ecotourism Centre (KKE) provides economic prosperity, ecological stability and social equity in the tribal area. The aim of the study was to measure the recreational value of the KKEC. Nearly 53 per cent of the visitors were 22 to 45 years age group with average annual household income of ` 3.75 Lakh and coming from 51.81 km range at the rate of 1.91 times in a year. About 52 per cent of ecotourists visited mainly for recreational purpose. The recreational demand of the KKEC was estimated by Travel Cost Method (TCM). The total travel cost and distance were negatively significant and education was positively significant. The value of individual consumer surplus per visit was about ` 215 and total consumer surplus of the KKEC was ` 7.52 crore per year which captured the recreational value of the site. Hence, an existing entry fee may also be hiked from ` 50 to 100 for an adult and ` 75 for a non-adult per trip to maximize the profit and further investment in the KKEC.